PEOPLE’S PERCEPTIONS OF THE CHANGING CLIMATE AND HUMAN INFLUENCE IN KATSINA STATE, NORTH-WESTERN NIGERIA (FUDMA JOURNAL OF SCIENCES, 2023)
Scientists recently reach a consensus that the climate change experienced currently is an outcome of human activities and this has been proven through the tests by atmospheric models and the measurable investigations of verifiable information records. This article aimed to assess the perception of the indigenes of Katsina state on the human influence in relation to the current changing climate through a larger step to cover both the urban and rural areas. 100 Questionnaire and/or a checklist interview were conducted from two sources (local government headquarter and weekly markets) in the seven oldest local governments of the state leaving us with 1387 respondents. Results on the observed changes revealed that reduction in the amount of rainfall received per year has the highest mean score of 56.7 while the increase in temperature has the lowest mean score value of 30.1. the view on presumable causes of climate change revealed that respondents with the opinion that climate change is a natural process destined by God has the highest mean score of 58.4, followed by those with the view of technological development through emissions from engines having a mean score of 55.7. Deforestation and Urbanisation have the mean score of 52.9 and 31.1 respectively. This means a high number of people in the state are not well informed about human influence to climate change. For these reasons, government and other stakeholders should extend their climate change awareness campaign deep into the rural communities where no care is given to environment sustainability issues.
Keywords: Climate change; Human Influence; Indigenes; Katsina state; Perception